Ceramic sand-based light ultra-high performance concrete and preparation method thereof

By using ceramic sand and copper-plated steel fibers in ultra-high performance concrete, combined with particle size optimization and slurry calculation technology, the problems of high density and high shrinkage rate of UHPC are solved, and lightweight with low density, high strength and low shrinkage rate are prepared. Ultra-high performance concrete, meets the needs of lightweight materials and reduces costs.

CN119285293APending Publication Date: 2025-01-10CHINA THREE GORGES UNIV

Patent Information

Application Number
CN202411352862.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing ultra-high performance concrete (UHPC) materials have high density and high shrinkage rate, which limits their wide application in lightweight and low shrinkage occasions.

Method used

Ceramic sand is used as a light aggregate, combined with the optimized particle grading design and copper-plated steel fibers, particle size distribution is optimized through the Andreasen stacking model and compressible stacking model, and the slurry volume is accurately calculated using the excess slurry theory to prepare Lightweight ultra-high performance concrete with low apparent density, high strength and good durability.

Benefits of technology

It significantly reduces the density and shrinkage rate of concrete, improves toughness and crack resistance, achieves high bulk density and volume stability, meets the needs of lightweight materials, and reduces costs, and realizes the reuse of solid waste.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119285293A_ABST
    Figure CN119285293A_ABST
Patent Text Reader

Abstract

The invention relates to pottery sand light ultra-high performance concrete and a preparation method thereof, aims to solve the problems of large density and large shrinkage of traditional ultra-high performance concrete, and prepares the light ultra-high performance concrete with apparent density of 2000kg / m or less and strength of 110MPa or more by adopting pottery sand as a light aggregate and optimizing grain composition of the pottery sand and a cementing material. According to the technical scheme, the preparation method comprises the following steps: selecting cement, fly ash, silica fume and multi-particle-size pottery sand in a specific proportion, determining an optimal mixing proportion through Andriasen and a compressible stacking model, and adding copper-plated steel fibers to improve mechanical properties; the material cost, self weight and shrinkage rate are effectively reduced, and the prepared concrete has good fluidity and volume stability, is environment-friendly and energy-saving, improves the construction efficiency and structural durability, has wide building application prospects, is especially suitable for the engineering field sensitive to self weight and requiring high strength, and has wide application prospects. And a new path is provided for promoting light-weight and high-performance development of building materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and specifically relates to a ceramic sand-based lightweight ultra-high performance concrete and a preparation method thereof. Background Art

[0002] Ultra-High Performance Concrete (UHPC) is a new type of building material. It has been widely used in engineering fields such as bridges, buildings, and tunnels due to its outstanding physical and mechanical properties and excellent durability. The typical characteristics of UHPC are that its compressive strength is usually not less than 120 MPa, its tensile strength is not less than 10 MPa, and its durability is far superior to ordinary concrete. However, despite the many advantages of UHPC, its high density (usually greater than 2500kg / m³) and large shrinkage rate have become key factors limiting its promotion and application.

[0003] In response to the high density and shrinkage of UHPC, researchers have developed Lightweight Ultra-High Performance Concrete (LUHPC). LUHPC uses lightweight aggregates to partially or completely replace the fine aggregates in UHPC to reduce the concrete's bulk density and improve its shrinkage performance. The introduction of lightweight aggregates can not only effectively reduce the density of LUHPC, but also release the internally stored moisture during the hardening process of the paste, which plays an internal curing role on the structure, thereby reducing shrinkage and improving mechanical properties.

[0004] As a common solid waste, ceramic sand has become one of the ideal lightweight aggregates for preparing LUHPC due to its porous structure and good thermal insulation properties. The porous structure of ceramic sand can release moisture during the hardening process of concrete, which helps to reduce shrinkage and improve the mechanical properties of concrete. In addition, the low thermal conductivity of ceramic sand (usually no more than 0.23W / (mK)) enables it to have good thermal insulation and heat preservation capabilities, meeting the energy-saving and environmental protection needs of various types of buildings.

[0005] In the mix design of LUHPC, the most dense packing theory is a commonly used design method. By adjusting the distribution of different material particle sizes to optimize the particle packing state, improve the packing density and raw material utilization efficiency, and thus improve the performance and cost-effectiveness of LUHPC. The Andreasen packing model and the compressible packing model (CPM) are the most commonly used particle packing models. The Andreasen model is based on the continuous grading theory and has a high adjustment flexibility; while the CPM model takes into account the actual compaction of aggregates and achieves a tighter packing between aggregates through physical methods.

[0006] However, existing lightweight ultra-high performance concrete preparation technologies still have certain limitations. For example, some methods are cumbersome and fail to fully consider the special properties of lightweight aggregates, resulting in the final product's mechanical properties or economy not being optimal. In addition, although some technologies reduce the density of concrete, they fail to effectively solve the brittleness problem of UHPC, making the material prone to brittle failure when subjected to impact or dynamic loads.

[0007] In summary, in order to overcome the deficiencies of the prior art, the present invention provides a ceramic sand lightweight ultra-high performance concrete and a preparation method thereof. The invention optimizes the particle grading of ceramic sand and cementitious materials, uses the excess slurry theory to accurately calculate the slurry amount, and introduces copper-plated steel fibers to improve the toughness of concrete, thereby successfully preparing a lightweight ultra-high performance concrete with low apparent density, high strength, good durability, and excellent volume stability, which has important practical application value. Summary of the invention

[0008] The technical problem to be solved by the present invention is to provide a ceramic sand lightweight ultra-high performance concrete and a preparation method thereof, so as to solve the problems of high density and high shrinkage rate of existing ultra-high performance concrete (UHPC) materials in application, which limit the wide application of UHPC in occasions requiring light weight and low shrinkage.

[0009] In order to solve the above technical problems, the technical solution adopted by the present invention is a ceramic sand lightweight ultra-high performance concrete, which comprises the following raw material components in weight ratio: cement 628kg / m³~637kg / m³, fly ash 179kg / m³~209kg / m³, silica fume 149kg / m³~195kg / m³, ceramic sand with a particle size range of 0.3mm~0.6mm 184kg / m³~294kg / m³, and particle size range of 0. 118kg / m³~192kg / m³ of ceramic sand with a particle size range of 6mm~1.18mm, 176kg / m³~208kg / m³ of ceramic sand with a particle size range of 1.18mm~2.36mm, 180kg / m³ of water, 2.5% of the polycarboxylic acid water-reducing agent in the amount of the cementitious material, and 1.5%~3% of the volume of copper-plated steel fiber; wherein the mass ratio of the cementitious material to the ceramic sand is 1.7:1, and the water-cement ratio is 0.18.

[0010] In a preferred embodiment, the cylinder compressive strength of the ceramic sand is not less than 6.8 MPa, and the water absorption rate is not higher than 16.34%.

[0011] In a preferred embodiment, after the ceramic sand is screened, the bulk densities of ceramic sand with particle sizes of 0.3mm~0.6mm, 0.6mm~1.18mm, and 1.18mm~2.36mm are 740.32kg / m³, 598.34kg / m³, and 548.56kg / m³, respectively, and the apparent densities are 1875kg / m³, 1685kg / m³, and 1500kg / m³, respectively.

[0012] In a preferred embodiment, the weight ratio of the components in the cementitious material is cement: fly ash: silica fume = 0.64: ​​0.21: 0.15, or cement: fly ash: silica fume = 0.62: 0.18: 0.20, and the ratio is calculated by the Andreasen stacking model and the compressible stacking model.

[0013] In the preferred embodiment, the copper-plated steel fiber is linear, has a length of 13 mm, a diameter of 0.2 mm, a tensile strength of 2850 MPa, an elastic modulus of 200 GPa, and a density of 7850 kg / m³.

[0014] A method for preparing any one of the above-mentioned ceramic sand lightweight ultra-high performance concrete comprises the following steps: Step 1: Put the cementitious material and pottery sand into a mixing pot and mix them according to the ratio design; Step 2: Add the mixed solution of polycarboxylate water reducer and water into the stirring pot twice, with an interval of no more than 1 minute between each addition and stir thoroughly; Step 3: Slowly sprinkle the copper-plated steel fiber in the slurry during stirring, and continue stirring until the steel fiber is evenly distributed in the slurry to obtain a slurry; Step 4: Pour the obtained slurry into a mold for forming, and obtain a ceramic sand lightweight ultra-high performance concrete specimen after curing.

[0015] In a preferred embodiment, the slump of the slurry obtained in Step 3 is 150 mm to 180 mm, and the density after entering the mold is 1910 kg / m³ to 1990 kg / m³.

[0016] In a preferred solution, the curing step in Step 4 is to carry out curing with the mold and film for one day and then move the mold into a standard curing room for curing for up to 28 days.

[0017] In the preferred embodiment, the density of the ceramic sand lightweight ultra-high performance concrete specimen prepared in the Step 4 is 1900kg / m³~2000kg / m³, the compressive strength is 110MPa~130MPa, the axial compressive strength is 95MPa~120MPa, the axial tensile strength is 3.5MPa~6MPa, the flexural strength is 9MPa~15MPa, the shear strength is 22MPa~29MPa, and the elastic modulus is 30GPa~34GPa.

[0018] The present invention provides a ceramic sand-based lightweight ultra-high performance concrete and a preparation method thereof, which has the following beneficial effects: 1. The present invention solves the problems of high density and high shrinkage rate in the application of existing ultra-high performance concrete (UHPC) materials; 2. The present invention introduces pottery sand as light aggregate and combines it with optimized particle grading design, so that the apparent density of the concrete prepared is significantly reduced and the shrinkage performance is improved, thus meeting the needs of different projects for light materials; 3. The porous structure of the ceramic sand of the present invention can release the water stored inside during the hardening process of concrete, playing the role of internal curing, thereby effectively reducing the shrinkage rate of concrete and improving the volume stability of concrete; 4. The addition of the copper-plated steel fiber of the present invention significantly improves the toughness and crack resistance of the concrete, so that the concrete prepared therefrom can exhibit better mechanical properties when subjected to impact or dynamic loads; 5. The present invention uses the improved Andreasen stacking model and compressible stacking model to optimize the particle gradation of lightweight aggregate and cementitious material, which can save cement consumption and reduce costs while maintaining the excellent performance of UHPC. The excess slurry theory is used to calculate the slurry volume to avoid insufficient slurry due to the porous characteristics of ceramic sand, insufficient slurry wrapping the aggregate, which increases the friction between the aggregate particles and reduces the fluidity of the slurry, thereby achieving high packing density and volume stability; 6. The shale pottery sand of the present invention is a lightweight building material made by crushing and burning clay shale. The use of pottery sand as a lightweight aggregate to prepare lightweight ultra-high performance concrete can effectively reduce the apparent density of ultra-high performance concrete. The porous characteristics of the pottery sand can improve the problem of large shrinkage of ultra-high performance concrete. In addition, the pottery sand has a low thermal conductivity, usually not exceeding 0.23W / (mK), which shows that it has good thermal insulation capabilities and meets the needs of various types of buildings. 7. The bridging effect of the steel fiber of the present invention will have a restraining effect on the matrix, increase the toughness of the matrix to resist shrinkage, so as to achieve the inhibition of UHPC shrinkage. The steel fiber itself has a high elastic modulus, which provides a skeleton support effect when the concrete undergoes shrinkage deformation, which helps to reduce its early shrinkage deformation. The steel fiber can improve the toughness of the concrete, so that the concrete, which is originally a brittle material, becomes a composite material with certain plastic properties. When subjected to impact or dynamic loads, the steel fiber concrete can better absorb energy, reduce the risk of brittle failure, and help resist shrinkage; 8. The ceramic sand lightweight ultra-high performance concrete prepared by the present invention has an apparent density of 1900-2000, a slump of 150mm-180mm, a compressive strength of 110MPa-130MPa, an elastic modulus of 30GPa-34GPa, and a 60d shrinkage strain of 551-641. It is a lightweight ultra-high performance concrete with good homogeneity and volume stability, and also has good tensile, flexural and shear strengths; 9. The ceramic sand lightweight ultra-high performance concrete prepared by the present invention has been tested by ultrasonic wave velocity, with a wave velocity of 3.541km / s~3.743km / s and a porosity of 3.51%~3.92%, and the performance test results are excellent; 10. The present invention reduces the manufacturing cost of concrete by optimizing the mix ratio and using cheap alternative materials (such as fly ash, silica fume and pottery sand). The preparation method is simple and easy, does not require complex equipment and special operating skills, and is easy to promote and apply; 11. The present invention uses pottery sand as light aggregate, which not only reduces the cost but also realizes the recycling of solid waste, and has good economic and environmental effects. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a flow chart of the pouring steps of ceramic sand lightweight UHPC of Examples 4 to 8 of the present invention; Figure 2 This is a schematic diagram of the failure morphology of the axial tensile test of the sand lightweight UHPC in Example 4 of the present invention; Figure 3 This is a schematic diagram of the failure morphology of the flexural test of the sand lightweight UHPC in Example 5 of the present invention; Figure 4 This is a schematic diagram of the failure morphology of the shear test of the sand lightweight UHPC in Example 6 of the present invention; Figure 5 Schematic diagram of shrinkage strain of ceramic sand lightweight UHPC at different ages in Examples 4 to 8 of the present invention; Figure 6 This is a SEM image of the microstructure of the ceramic sand lightweight UHPC in Example 4 of the present invention. DETAILED DESCRIPTION

[0020] The present invention will be further described below in conjunction with the accompanying drawings and implementation examples: Example 1 A ceramic sand lightweight ultra-high performance concrete comprises the following raw material components in weight ratio: 628kg / m³~637kg / m³ of cement, 179kg / m³~209kg / m³ of fly ash, 149kg / m³~195kg / m³ of silica fume, 184kg / m³~294kg / m³ of ceramic sand with a particle size range of 0.3mm~0.6mm, 118kg / m³~192kg / m³ of ceramic sand with a particle size range of 0.6mm~1.18mm, 176kg / m³~208kg / m³ of ceramic sand with a particle size range of 1.18mm~2.36mm, 180kg / m³ of water, a polycarboxylate water reducer in an amount of 2.5% of the mass of the cementitious material, and 1.5%~3% of copper-plated steel fiber in a volume amount; wherein the mass ratio of the cementitious material to the ceramic sand is 1.7:1, and the water-cement ratio is 0.18.

[0021] In this embodiment, the cylinder compressive strength of the ceramic sand is not less than 6.8 MPa, and the water absorption rate is not higher than 16.34%.

[0022] Furthermore, after screening, the bulk densities of the ceramic sand with particle sizes of 0.3mm~0.6mm, 0.6mm~1.18mm, and 1.18mm~2.36mm are 740.32kg / m³, 598.34kg / m³, and 548.56kg / m³, respectively, and the apparent densities are 1875kg / m³, 1685kg / m³, and 1500kg / m³, respectively.

[0023] Furthermore, the weight ratio of each component in the cementitious material is cement: fly ash: silica fume = 0.64: ​​0.21: 0.15, or cement: fly ash: silica fume = 0.62: 0.18: 0.20, and the ratio is calculated by the Andreasen stacking model and the compressible stacking model.

[0024] Furthermore, the copper-plated steel fiber is linear, has a length of 13 mm, a diameter of 0.2 mm, a tensile strength of 2850 MPa, an elastic modulus of 200 GPa, and a density of 7850 kg / m³.

[0025] Example 2 In another preferred embodiment, based on the above embodiment 1, a method for preparing any one of the above-mentioned ceramic sand lightweight ultra-high performance concrete comprises the following steps: Step 1: Put the cementitious material and pottery sand into a mixing pot and mix them according to the ratio design; Step 2: Add the mixed solution of polycarboxylate water reducer and water into the stirring pot twice, with an interval of no more than 1 minute between each addition and stir thoroughly; Step 3: Slowly sprinkle the copper-plated steel fiber in the slurry during stirring, and continue stirring until the steel fiber is evenly distributed in the slurry to obtain a slurry; Step 4: Pour the obtained slurry into a mold for forming, and obtain a ceramic sand lightweight ultra-high performance concrete specimen after curing.

[0026] In this embodiment, the slump of the slurry obtained in Step 3 is 150 mm to 180 mm, and the density after entering the mold is 1910 kg / m³ to 1990 kg / m³.

[0027] Furthermore, the curing step in Step 4 is to carry out curing with the mold and film for one day, and then move the mold into a standard curing room for curing for 28 days.

[0028] Furthermore, the density of the ceramic sand lightweight ultra-high performance concrete specimen prepared in the Step 4 is 1900kg / m³~2000kg / m³, the compressive strength is 110MPa~130MPa, the axial compressive strength is 95MPa~120MPa, the axial tensile strength is 3.5MPa~6MPa, the flexural strength is 9MPa~15MPa, the shear strength is 22MPa~29MPa, and the elastic modulus is 30GPa~34GPa.

[0029] Example 3 In another preferred embodiment, on the basis of the above-mentioned embodiments 1 and 2, in the following embodiment, cement uses P·O52.5 grade ordinary Portland cement, fly ash uses ultrafine fly ash, pottery sand uses shale pottery sand, polycarboxylic acid high-performance water-reducing agent uses polycarboxylic acid high-performance water-reducing agent with a water reduction rate of 35%, and copper-plated steel fiber uses linear copper-plated steel fiber, wherein the particle size range of pottery sand is 0~3mm, the apparent density is 1835kg / m3, the bulk density is 819kg / m3, the cylinder pressure strength is 6.8MPa, and the water absorption rate is 16.3%.

[0030] Example 4 In another preferred embodiment, based on the above-mentioned embodiment 3, the mass of the cementitious material and the ceramic sand is weighed according to the Andreasen stacking model design mix ratio, and the specific design mix ratio is shown in the following table 1 mix ratio 1: Table 1 Mixing ratio 1 (unit: kg / m 3 )

[0031] The lightweight ultra-high performance concrete prepared by the above mix ratio 1 has a slump test of 188 mm and an apparent density of 1919 kg / m 3The cube compressive strength is 111.3MPa, the axial compressive strength is 97.7 MPa, the axial tensile strength is 3.56MPa, the flexural strength is 9.61 MPa, the shear strength is 22 MPa, the elastic modulus is 30.84 GPa, the 60-day shrinkage strain is 641, the porosity is 3.59%, and the micromorphology SEM picture is as follows Figure 6 shown.

[0032] Example 5 In another preferred embodiment, based on the above embodiment 4, the volume content of steel fiber is adjusted to 2%, and other proportions remain unchanged, as shown in the following table 2, proportion 2: Table 2 Mix ratio 2 (unit: kg / m 3 )

[0033] The lightweight ultra-high performance concrete prepared by the above mix ratio 2 has a slump test of 181 mm and an apparent density of 1948 kg / m 3 The cube compressive strength is 115.7MPa, the axial compressive strength is 106.3MPa, the axial tensile strength is 3.84MPa, the flexural strength is 11.56MPa, the shear strength is 23.72MPa, the elastic modulus is 31.79GPa, the 60-day shrinkage strain is 612, and the porosity is 3.69%.

[0034] Example 6 In another preferred embodiment, based on the above embodiment 5, the volume content of steel fiber is adjusted to 3%, and other proportions remain unchanged, as shown in the following table 3: Table 3 Mixing ratio 3 (unit: kg / m 3 )

[0035] The lightweight ultra-high performance concrete prepared by the above mix ratio 3 has a slump test of 150 mm and an apparent density of 1977 kg / m 3 The cube compressive strength is 125.4MPa, the axial compressive strength is 115.3MPa, the axial tensile strength is 5.94MPa, the flexural strength is 14.44MPa, the shear strength is 28.15MPa, the elastic modulus is 33.55GPa, the 60-day shrinkage strain is 551, and the porosity is 3.92%.

[0036] Example 7 In another preferred embodiment, based on the above embodiment 3, in Step 1, the masses of the cementitious material and the ceramic sand are weighed according to the compressible stacking model design mix ratio, as shown in the following Table 4 Mix Ratio 4: Table 4 Mixing ratio 4 (unit: kg / m 3 )

[0037] The lightweight ultra-high performance concrete prepared by the above mix ratio 4 has a slump test of 230 mm and an apparent density of 1961 kg / m 3 The cube compressive strength is 117.1MPa, the axial compressive strength is 108.7MPa, the axial tensile strength is 4.1MPa, the flexural strength is 11.03MPa, the shear strength is 23.45 MPa, the elastic modulus is 31.58 GPa, the 60-day shrinkage strain is 627, and the porosity is 3.51%.

[0038] Example 8 In another preferred embodiment, based on the above embodiment 7, the volume content of steel fiber is adjusted to 2%, and other proportions remain unchanged, as shown in the following table 5, proportion 5: Table 5 Mixing ratio 5 (unit: kg / m 3 )

[0039] The lightweight ultra-high performance concrete prepared by the above mix ratio 4 has a slump test of 217 mm and an apparent density of 1982 kg / m 3 The cube compressive strength is 124.6MPa, the axial compressive strength is 116.1MPa, the axial tensile strength is 4.83MPa, the flexural strength is 13.2MPa, the shear strength is 24.46 MPa, the elastic modulus is 32.78GPa, the 60-day shrinkage strain is 603, and the porosity is 3.62%.

[0040] Example 9 In another preferred embodiment, based on the above embodiments 3 to 8, the mixing step of the above embodiment is as follows: Figure 1 As shown: 1) According to the mix ratio of ceramic sand lightweight ultra-high performance concrete designed by the Andreasen model and the compressible stacking model, the cementitious material and ceramic sand are added into a pre-wetted mixing pot and stirred for 100 seconds to fully mix them; 2) Mix water and water reducer and stir, slowly add 2 / 3 of the mixture into the mixing pot, add the remaining mixture after 30 seconds, and stir for 300 seconds to make it fully contact with cement and make the cement hydration more complete; 3) After the slurry is formed, continue to stir and slowly sprinkle the steel fiber into the slurry. Stir for another 180 seconds to ensure that the steel fiber is evenly distributed in the slurry. 4) The slump of the freshly mixed slurry is 150mm~190mm, and the wet apparent density is 1930kg / m3~1990kg / m3.

[0041] Example 10 In another preferred embodiment, based on the above embodiments 3 to 9, the molding and curing steps of the test piece in the above embodiment are: 1) Pour the freshly mixed slurry into the mold for forming. Pour the slurry into the mold 1 / 2 for 20 times, for a total of 40 times, and then vibrate for 20 seconds. Finally, scrape off the excess concrete and smooth it. 2) After the slurry has initially set, it is coated and moved into a standard curing box for curing for 1 day before demoulding; 3) After demoulding, the specimens were placed in a standard curing box for curing for 28 days to obtain ceramic sand lightweight ultra-high performance concrete specimens.

[0042] Finally, the specimens of Examples 4 to 8 cured for 28 days were subjected to mechanical property and shrinkage property tests, and the test results were shown in Tables 6 and 7 below: Table 6 Mechanical properties test results of ceramic sand lightweight ultra-high performance concrete described in Examples 4 to 8

[0043] The failure morphology of the axial tensile test of ceramic sand lightweight UHPC in Examples 4 to 8 is shown in Figure 2 The failure mode of the flexural specimen is shown in Figure 3 The failure mode of the shear specimen is shown in Figure 4 .

[0044] Table 7 Shrinkage strain (με) of ceramic sand lightweight ultra-high performance concrete described in Examples 4 to 8

[0045] The shrinkage strain of ceramic sand lightweight UHPC at different ages in Examples 4 to 8 is shown in Figure 5 .

[0046] The ultrasonic wave velocities of the ceramic sand lightweight ultra-high performance concrete described in Examples 4 to 8 are 3.541 km / s, 3.672 km / s, 3.743 km / s, 3.671 km / s and 3.719 km / s, respectively, and the porosities are 3.59%, 3.69%, 3.92%, 3.51% and 3.62%, respectively.

[0047] The results show that the ceramic sand lightweight ultra-high performance concrete prepared by the preparation method of the present invention can achieve various properties of apparent density below 1990kg / m3, slump above 150mm, compressive strength above 110MPa, and has good homogeneity and volume stability.

[0048] In summary, the ceramic sand lightweight ultra-high performance concrete and its preparation method proposed in the present invention use ceramic sand as lightweight aggregate, and combine with cement, fly ash, silica fume and other cementitious materials, as well as copper-plated steel fiber, polycarboxylic acid water reducer and other additives to form a new material combination. This combination significantly reduces the weight and cost of the material while maintaining the high strength and durability of UHPC (ultra-high performance concrete); the particle size distribution of ceramic sand and cementitious materials is accurately calculated and optimized using the Andreasen stacking model and the compressible stacking model (CPM), and the optimal particle size distribution is obtained. The particle size optimization technology effectively improves the packing density and strength of the material and reduces the shrinkage rate; the excess slurry theory is used to calculate the demand for slurry material, ensuring the accurate slurry ratio under the porous characteristics of ceramic sand, further improving the volume stability and performance of the material; the selection of ceramic sand with special properties puts forward clear requirements on the physical properties of ceramic sand, such as cylinder pressure strength ≥68MPa, water absorption rate ≤16.34%. The selection of this high-performance ceramic sand has a positive effect on improving the overall performance of LUHPC; the present invention innovatively combines the Andreasen stacking model and the compressible The combined use of the stacking model has double optimized the particle size distribution of ceramic sand and cementitious materials, overcoming the limitations of a single model in material ratio design and significantly improving the density and performance of the material; its unique excess slurry calculation method uses excess slurry theory to accurately calculate the demand for slurry materials. This method fully considers the porous characteristics of ceramic sand, avoids the problem of under-calculation of slurry due to ceramic sand pores, and improves the accuracy and scientificity of material ratios; by introducing high-performance ceramic sand, copper-plated steel fiber, polycarboxylic acid water-reducing agent and other materials, combined with advanced preparation technology, it has successfully prepared LUHPC has low density, high strength, low shrinkage and high durability, which has achieved significant performance improvement and application expansion on the basis of traditional UHPC; using ceramic sand, a solid waste, as lightweight aggregate not only solves the waste disposal problem, but also reduces the production cost of LUHPC, reflecting the dual considerations of environmental protection and economic benefits of this invention; the present invention effectively improves the microscopic pore structure of LUHPC, enhances the material's impermeability and durability, opens up a new path for the research and development and application of green building materials, and shows broad market application prospects and far-reaching industry impact.

Claims

1. A ceramic sand lightweight ultra-high performance concrete, characterized in that: The invention comprises the following raw material components in weight ratio: 628kg / m³~637kg / m³ of cement, 179kg / m³~209kg / m³ of fly ash, 149kg / m³~195kg / m³ of silica fume, 184kg / m³~294kg / m³ of pottery sand with a particle size range of 0.3mm~0.6mm, 118kg / m³~192kg / m³ of pottery sand with a particle size range of 0.6mm~1.18mm, 176kg / m³~208kg / m³ of pottery sand with a particle size range of 1.18mm~2.36mm, 180kg / m³ of water, a polycarboxylate water reducer in an amount of 2.5% of the mass of the cementitious material, and 1.5%~3% of copper-plated steel fiber in a volume amount; wherein the mass ratio of the cementitious material to the pottery sand is 1.7:1, and the water-to-cement ratio is 0.

18.

2. The ceramic sand lightweight ultra-high performance concrete according to claim 1, characterized in that: The cylinder compressive strength of the ceramic sand is not less than 6.8MPa, and the water absorption rate is not higher than 16.34%.

3. The ceramic sand lightweight ultra-high performance concrete according to claim 2, characterized in that: After screening, the bulk densities of the ceramic sand with particle sizes of 0.3mm~0.6mm, 0.6mm~1.18mm, and 1.18mm~2.36mm are 740.32kg / m³, 598.34kg / m³, and 548.56kg / m³, respectively, and the apparent densities are 1875kg / m³, 1685kg / m³, and 1500kg / m³, respectively.

4. The ceramic sand lightweight ultra-high performance concrete according to claim 1, characterized in that: The weight ratio of each component in the cementitious material is cement: fly ash: silica fume = 0.64: ​​0.21: 0.15, or cement: fly ash: silica fume = 0.62: 0.18: 0.20, and the ratio is calculated by the Andreasen stacking model and the compressible stacking model.

5. The ceramic sand lightweight ultra-high performance concrete according to claim 1, characterized in that: The copper-plated steel fiber is linear, with a length of 13 mm, a diameter of 0.2 mm, a tensile strength of 2850 MPa, an elastic modulus of 200 GPa, and a density of 7850 kg / m³.

6. A method for preparing a ceramic sand lightweight ultra-high performance concrete according to any one of claims 1 to 5, characterized in that: The following steps are involved: Step 1: Put the cementitious material and pottery sand into a mixing pot and mix them according to the ratio design; Step 2: Add the mixed solution of polycarboxylate water reducer and water into the stirring pot twice, with an interval of no more than 1 minute between each addition and stir thoroughly; Step 3: Slowly sprinkle the copper-plated steel fiber into the slurry during stirring, and continue stirring until the steel fiber is evenly distributed in the slurry to obtain a slurry; Step 4: Pour the obtained slurry into a mold for forming, and obtain a ceramic sand lightweight ultra-high performance concrete specimen after curing.

7. The method for preparing a lightweight ultra-high performance concrete according to claim 6, characterized in that: The slump of the slurry obtained in the Step 3 is 150 mm to 180 mm, and the density after being molded is 1910 kg / m³ to 1990 kg / m³.

8. The method for preparing a ceramic sand lightweight ultra-high performance concrete according to claim 7, characterized in that: The curing steps in Step 4 are: after one day of curing with mold and film, move into a standard curing room and cure for up to 28 days.

9. The method for preparing a ceramic sand lightweight ultra-high performance concrete according to claim 8, characterized in that: The ceramic sand lightweight ultra-high performance concrete specimen prepared in the Step 4 has a density of 1900kg / m³~2000kg / m³, a compressive strength of 110MPa~130MPa, an axial compressive strength of 95MPa~120MPa, an axial tensile strength of 3.5MPa~6MPa, a flexural strength of 9MPa~15MPa, a shear strength of 22MPa~29MPa, and an elastic modulus of 30GPa~34GPa.

Citation Information

Patent Citations

  • Light low-shrinkage super-high performance concrete and preparation method thereof

    CN107935505A

  • Autoclaving-free light ultra-high-performance concrete and preparation method thereof

    CN110054457A

  • Ultra-high performance lightweight concrete taking pottery sand as lightweight aggregate and preparation method thereof

    CN112125603A

  • Internal curing low-shrinkage lightweight aggregate ultra-high performance concrete and preparation method thereof

    CN113321467A

  • Lightweight low-shrinkage ultra-high performance concrete and preparation method thereof

    CN114455907A

Cited By

  • Lightweight sand modified ultra-high strain hardening ultra-high performance concrete

    CN121181311A